Structural Characteristics and their Significance for Hydrocarbon Accumulation in the Northern Slope of the Central Sichuan Paleo‐uplift - TIAN, Xingwang; LIU, Guangdi; LUO, Bing; YANG, Yu; WEN, Long; ZHANG, Benjian; CHEN, Xiao; SU, Guiping; SONG, Zezhang; PENG, Hanlin; ZHOU, Gang; YAN, Wei; et al. (Acta geologica Sinica (Beijing), 2022)
Based on 2D and 3D seismic data, the latest drilling data and field outcrop data of the northern slope of the Central Sichuan paleo‐uplift, the structural analysis method is used to analyze unconformity development characteristics and fault characteristics during the key structural transformation period, discussing the influence of the structural characteristics on the hydrocarbon accumulation of deep carbonate rocks. The results show that: (1) The two key unconformities of the Tongwan and Caledonian periods were primarily developed in deep carbonate rocks. Firstly, Tongwan's unconformities are characterized by regional disconformities between the second and third members of the Dengying Formation, the top formation of the Sinian and the lower Cambrian, strips of which zigzag through the north and south sides of the study area. Secondly, the Caledonian unconformity is characterized by a regional unconformable contact between the lower Permian and the ower Paleozoic strata. From NE to SW, the age of the strata, which were subject to erosion, changes from new to old, the denudation distribution showing as a nose‐shaped structure which inclines towards the ENE. (2) Boundary fault and transtensional strike‐slip faults developed in the Sinian to Paleozoic strata. In profile, there are three types of structural styles: steep and erect, flower structures, ‘Y’ and reversed ‘Y’ type faults. In plane view, the Sinian developed extensional boundary faults extending in an almost NS direction, strike‐slip faults developing and extending linearly in approximately EW, WNW and NE strikes in the Cambrian, with characteristically more in the south and less in the north. (3) The faults in the northern slope show obvious zonal deformations in transverse view as well as significant stages and stratified activity in a longitudinal direction. Among them, the activity of faults in the Sinian was the strongest, followed by the activity in the Cambrian period, the activity intensity of faults in the Permian period being the weakest. This fault activity can be divided into four periods: Sinian, Cambrian‐Permian, the early Indosinian period and the late Indosinian‐Himalayan period, the transtensional strike‐slip faults being the products of oblique extensions of pre‐existing weak zones in the Xingkai and Emei taphrogenesis, with a particular inheritance in the main faults. (4) Combined with hydrocarbon accumulation factors, it is considered that the epigenetic karstification of the Tongwan and Caledonian unconformities in the northern slope controlled the formation and distribution of carbonate karst reservoirs over a large area, also acting as a good pathway for oil and gas migration. The extensional faults developed at the margin of the NS trending rift, controlling the sag‐platform sedimentary pattern in the Dengying Formation of the Sinian. Strike‐slip faults in NE, WNW and ENE directions may control the micro‐geomorphological pattern inside the platform and intensify the differential distribution of grain beach facies. The multi‐stage hereditary activity of strike‐slip faults not only improved the porosity and permeability of the reservoirs, but also acted as the main channel of oil and gas migration, providing favorable conditions for the development of the current multi‐layer gas‐bearing scenario in the northern slope of the Central Sichuan Basin.